Alternative protocol for the use of short-acting estrogen in the treatment of urinary incontinence in a spayed bitch: case report (Research, Society and Development, 2020)
Urinary incontinence is a change in urine storage that commonly affects sterilized bitches. Due to the hormonal correlation between the removal of gonads from females and the incompetence of the urethral sphincter mechanism, treatment with estrogen replacement can reverse this condition. However, the use of this hormone in dogs is to protocol within the dosage of the product. The response of each dog is individual and according to the clinical response, varying in quantity and time regardless of weight or size. Therefore, the objective of this report was to demonstrate a possible dose and time interval in the treatment of urinary incontinence in a castrated dog. A female, castrated dog, aged approximately 10 years, with urinary incontinence, and stabilization of the clinical condition with 0.25 mg/animal of estriol (Incurin®) was attended to every 72 hours, demonstrating that the institution of therapy in some individuals may differ markedly from the recommended 1 mg/animal package insert every 24 hours.